Pengaruh Citra Merek dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan di PT. Supra Primatama Nusantara Cabang Sukabumi (Biznet) - Enjang Rusmana (Universitas Linggabuana PGRI Sukabumi, 2021)
The aim of the researchers in this research is to independently and simultaneously prove the effect of brand image and service quality on Biznet customer satisfaction in Sukabumi. This type of research is causal associative with quantitative methods. The population is all customers who have subscribed to the internet since the first time Biznet arrived in Sukabumi in July 2015 until June 2021 with a total of 4,121 customers with a sample of 97 people taken from slovin results with an error rate of 10%. The sampling technique is by simple random sampling. Methods of analysis include data quality testing, analysis prerequisite tests, multiple linear regression analysis tests, KD analysis and hypothesis testing with the help of the SPSS v.26 statistical application. The result is that independently and simultaneously brand image and service quality have an influence on Biznet Sukabumi's customer satisfaction.